2021
DOI: 10.3390/cancers13205230
|View full text |Cite
|
Sign up to set email alerts
|

Oncomine™ Comprehensive Assay v3 vs. Oncomine™ Comprehensive Assay Plus

Abstract: The usage of next generation sequencing in combination with targeted gene panels has enforced a better understanding of tumor compositions. The identification of key genomic biomarkers underlying a disease are crucial for diagnosis, prognosis, treatment and therapeutic responses. The Oncomine™ Comprehensive Assay v3 (OCAv3) covers 161 cancer-associated genes and is routinely employed to support clinical decision making for a therapeutic course. An improved version, Oncomine™ Comprehensive Assay Plus (OCA-Plus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Differences in patient selection may be another explanation. In the study by Patch et al, 39% were platinum-sensitive and 61% were platinum-resistant or -refractory, while TCGA included 69% platinum-sensitive and 31% platinum-resistant patients [10,11]. In TCGA and Patch et al, platinum status was defined as resistant if the patient had progressed or recurred within 6 months after the end of the last treatment, which is consistent with our definition.…”
Section: Mutation Profile In Danish Ovarian Cancer Patients Compared ...supporting
confidence: 76%
See 1 more Smart Citation
“…Differences in patient selection may be another explanation. In the study by Patch et al, 39% were platinum-sensitive and 61% were platinum-resistant or -refractory, while TCGA included 69% platinum-sensitive and 31% platinum-resistant patients [10,11]. In TCGA and Patch et al, platinum status was defined as resistant if the patient had progressed or recurred within 6 months after the end of the last treatment, which is consistent with our definition.…”
Section: Mutation Profile In Danish Ovarian Cancer Patients Compared ...supporting
confidence: 76%
“…The most extensive study based on data from the TCGA database showed TP53 mutations in 88% and BRCA1/2 mutations in 23% of 316 HGSC tumors [10]. Patch et al characterized the mutational profile of 80 HGSC patients [11]. They found TP53 mutations in 99% and BRCA1/2 mutations in 26%.…”
Section: Mutation Profile In Danish Ovarian Cancer Patients Compared ...mentioning
confidence: 99%
“…Moreover, analysis of the biomarkers MSI and TMB will help to select patients for immunotherapy. Other validation reports investigated a much lower number of genes, less variant types or biomarkers, or a much lower number of retro-or prospective diagnostic samples [21][22][23]. To assess the clinical value of the comprehensive TSO500 analysis compared to small panel screenings, we have set up the real-world BALLETT study (Belgian Approach of Local Laboratory Extensive Tumor Testing; https://clinicaltrials.gov/ ct2/show/NCT05058937, accessed on 5 May 2022) with the aim of introducing CGP for precision oncology and to increase treatment options for cancer patients in Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…All tumor specimens underwent comprehensive, targeted, next‐generation sequencing using the Oncomine assay at Yale Tumor Profiling Laboratory 28 . Briefly, the tumor percentage was visually estimated on hematoxylin‐and‐eosin–stained samples (or on immunohistochemical‐stained samples for some cases) by a molecular pathologist.…”
Section: Methodsmentioning
confidence: 99%